Предмет: Алгебра, автор: pina57375

помогите, пожалуйста.

Приложения:

Ответы

Автор ответа: asatryanm075
1

1) (4b-1)(4b+1)=16b²+1

2)(8m+3y)(3y-8m)=9y²-64m²

3)(0.3p³+0.2q⁴)(0.3p³-0.2q⁴)=0.09p⁶-0.04q⁸

4)(x⁴-y⁴)(x⁴+y⁴)(x⁸+y⁸)=(x⁸-y⁸)(x⁸+y⁸)=x¹⁶-y¹⁶

5)(m⁶-n⁵)(-m⁶-n⁵)=-(m⁶-n⁵)(m⁶+n⁵)=-(m¹²-n¹⁰)=-m¹²+n¹⁰

6)(1.3 {a}^{11}  +  \frac{2}{9}  {b}^{3} )( \frac{2}{9}  {b}^{3}  - 1.3 {a}^{11} ) =  \frac{4}{81}  {b}^{6}  - 1.69 {a}^{22}

Автор ответа: Katty20008
1

Відповідь:

1) (4b-1)(4b+1)=(4b)²-1²=16b²-1

2) (8m+3y)(3y-8m)=(3y+8m)(3y-8m)=(3y)²-(8m)²=9y²-64m²

3) (0,3p³+0,2q^{4})(0,3p³-0,2q^{4})=(0,3p³)²-(0,2q^{4})²=0,09p^{6}-0,02q^{8}

4) (x^{4}-y^{4})(x^{4}+y^{4})(x^{8}+y^{8})=((x^{4})²-(y^{4})²)(x^{8}+y^{8})=(x^{8}-y^{8})(x^{8}+y^{8})=(x^{8})²-(y^{8})²=x^{16}+y^{16}

5) (m^{6}-n^{5})(-m^{6}-n^{5})=(m^{6}-n^{5})(m^{6}+n^{5})*(-1)=((m^{6})²-(n^{5})²)*(-1)=(m^{12}-n^{10})*(-1)=-m^{12}+n^{10}= n^{10}-m^{12}

6) (1,3a^{11}+\frac{2}{9}b^{3})(\frac{2}{9}b^{3}-1,3a^{11})=(\frac{2}{9}b^{3}-1,3a^{11})(\frac{2}{9}b^{3}+1,3a^{11})=(\frac{2}{9}b^{3})²-(1,3a^{11})²=\frac{4}{81}b^{6}-1,69a²²

Пояснення:

Похожие вопросы